IMPACT OF DESIGN THINKING ON CONCEPTUAL DESIGN IN INTERIOR DESIGN STUDIO COURSES - Rashdan, Wael (PEOPLE: International Journal of Social Sciences, 2017)
Design thinking has gained prominence in teaching interior design studio courses. Exploring the applications of design thinking can help interior design students understand the complexity and importance of conceptual design, while also supporting their discovery of unique design approaches and innovative design solutions. This paper provides a review of literature on design thinking and design education, examining the factors that imply influence on design thinking application in interior design studio courses. This paper also discusses the impact of design-thinking applications on the design process, as well as its influence on conceptual design development within the context of interior design undergraduate education.